Post your question in the Comment section below, and a GRE expert will answer it as fast as humanly possible.

- Video Course
- Video Course Overview
- General GRE Info and Strategies - 7 videos (free)
- Quantitative Comparison - 7 videos (free)
- Arithmetic - 42 videos
- Powers and Roots - 43 videos
- Algebra and Equation Solving - 78 videos
- Word Problems - 54 videos
- Geometry - 48 videos
- Integer Properties - 34 videos
- Statistics - 28 videos
- Counting - 27 videos
- Probability - 25 videos
- Data Interpretation - 24 videos
- Analytical Writing - 9 videos (free)
- Sentence Equivalence - 39 videos (free)
- Text Completion - 51 videos
- Reading Comprehension - 16 videos

- Study Guide
- Philosophy
- Office Hours
- Extras
- Prices

## Comment on

Variables in Base and Exponent## How do we identify if we have

While solving this question, I considered 3 and -3 as the only answer since the rule says that base cannot be 1 and -1. Thinking it could be a trap answer. Could you please explain?

## If we're given a VARIABLE for

If we're given a VARIABLE for the base, then we need to consider whether or not that variable is 0, 1 or -1

For example, if we're told that x^y = x^3, then we can't automatically conclude that y = 3.

We can't make this conclusion, because there are certain values of x that don't work.

For example, if x = 1, the equation becomes 1^y = 1^3, in which case y can equal ANY number.

Likewise, if x = 0, the equation becomes 0^y = 0^3, in which case y can equal ANY number.

Alternatively, if we're explicitly told the value of the base AND that value is not 0, 1 or -1, then we can make solid conclusions. For example, if we're told that 5^x = 5^7, then we can be certain that x = 7

## For this type of question, if

By the way, thank you for all your prompt responses thus far.

## No, we can't make that

No, we can't make that conclusion.

In fact, even though x ≠ 0, it turns out that x = 1 and x = -1 ARE possible solutions to the equation.

Cheers,

Brent

## thanks admin, this question

## I had the same questions as

## I think it's time-consuming,

I think it's time-consuming, but possible to complete in that time frame.

## I got the right answers, but

1) At first I took 1 from each side:

x^(x^2-9) - 1 = 0

2) I figured that "x^(x^2-9)" would have to equal 1 since (1-1 = 0)

3) Then I just plugged in the numbers (9 was eliminated easily since the exponent was obviously too high). This method didn't seem to take too long to do, which was why I wanted to confirm if it's a correct way (as it's a "hard" question, but seemed too easy).

## That's a perfectly valid

That's a perfectly valid approach!

ASIDE: Steps 1 and 2 are really necessary. You used those steps to conclude that x^(x^2-9) = 1, even though that is the original equation :-)

## Nice explanation. Thanks

## I have a doubt regarding -1

-1^-8

=-[1/(1^8)]

=-[1/1]

=-1

which is not equal to 1

Hence answers should be 3,-3 and 1

Please help me understand how (-1) is a solution?

Thanks.

## Be careful. (-1)^(-8) does

Be careful. (-1)^(-8) does not equal = -[1/(1^8)]

The rule for negative exponents is: b^(-n) = 1/(b^n)

So, (-1)^-8 = 1/(-1)^8

= 1/1

= 1

Aside: Let's take a closer look at (-1)^8

(-1)^8 = (-1)(-1)(-1)(-1)(-1)(-1)(-1)(-1)

Find the product in PAIRS

(-1)(-1)(-1)(-1)(-1)(-1)(-1)(-1) = (1)(1)(1)(1)

= 1

Does that help?

Cheers,

Brent

## is -3^0=1 ? please i want to

## Any non-zero number to the

Any non-zero number to the power of 0 equals 1.

So, (-3)^0 = 1, (-4.55)^0 = 1, (19)^0 = 1, etc

Cheers,

Brent

## Hey Brent! How come at the

x^(x^2-9)=1

and changed the right side to x^0? I don't understand why you did that.

WHEW, it gets confusing writing exponents within exponents when you have to use ^.

Also, one other question, I knew that 1 raised to any power was equal to 1, but I didn't know if that same rule applied to -1. So is the rule that 1 OR -1 raised to any power is 1? If -1 was raised to an odd power, would it be -1?

## The goal with these kinds of

The goal with these kinds of questions is to rewrite expressions so that they have the same bases.

For example, we can take: 5^(x-4) = 25...

...and rewrite 25 to get: 5^(x-4) = 5^2

We can then write: x - 4 = 2

Etc.

The same applies to the following equation: x^(x^2-9) = 1

Does x does not equal 0, we know that x^0 = 1

So, we rewrite our equation as: x^(x^2-9) = x^0, at which point we can conclude that x^2 - 9 = 0

That's formalize the properties regarding 1 and -1 in the base:

PROPERTY #1: 1^k = 1 for ALL values of k

PROPERTY #2: (-1)^k = 1 for all EVEN values of k

PROPERTY #3: (-1)^k = -1 for all ODD values of k

For more on these properties, watch: https://www.greenlighttestprep.com/module/gre-powers-and-roots/video/1021